Comparison of pre- and postoperative pulmonary function in obese and non-obese female patients undergoing coronary artery bypass graft surgery - Akdur, Huelya; Yidit, Zerrin; Soezen, Ahmet Bilge; Cadatay, Tuelin; Gueven, Oezen (Wiley, 2006)
Objective and background: Various studies have suggested that body size and in-hospital mortality are related. However, only a few analysed the effects of obesity on pulmonary complications following coronary artery bypass graft surgery (CABG). The purpose of the present study was to assess early changes in lung volumes, respiratory complications and arterial blood gas tension following CABG in obese women. Methods: Pulmonary function tests (PFTs), treadmill exercise capacity tests (TM), arterial blood gases and pulmonary complications were studied in 124 obese (mean age 57.2 +/- 5.8 years) and 108 non-obese (mean age 58.6 +/- 5.9 years) female patients undergoing elective CABG. PFT, TM tests, arterial blood gas analyses and CXR were performed in the preoperative and postoperative periods and pulmonary complications were recorded. Breathing and coughing exercises, early ambulation and pulmonary clearing techniques were used by physical therapists to prevent pulmonary complications after CABG surgery. Results: Postoperative PFT and TM tests deteriorated significantly in both groups (P < 0.0001). The deterioration in the obese group was highly significant. The postoperative deterioration of blood gas measurements in obese patients was also statistically significant compared to non-obese patients. Early pulmonary complications developed in 21 (16.94%) of the obese patients and in 10 (9.25%) of non-obese patients. Duration of mechanical ventilation, intensive care unit and hospital stays were longer compared to the non-obese patients (P = 0.008, P < 0.0001, P = 0.0386, respectively). Conclusion: Obesity has a detrimental effect on pulmonary function, exercise capacity, blood gas measurements and complications rates in postoperative period following CABG surgery.
Keywords: coronary artery bypass surgery; obesity; pulmonary complication; women